EXTENDED STORAGE OF SUDANGRASS SEEDS - TOLEDO, MARIANA ZAMPAR; CAVARIANI, CLÁUDIO; NAKAGAWA, JOÃO; ALVES, ELZA (REVISTA BRASILEIRA DE MILHO E SORGO, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Sudangrass stands out for being tolerant to drought and saline stress. However, studies on production of seeds and post-harvest technologies are insufficient considering both the demand and potential of this crop. This study aimed to monitor physiological quality of sudangrass seeds stored under different environmental conditions for a period of 18 months. Sudangrass seeds were stored under four conditions (natural environment, dry chamber, frost free, freezer). Physiological quality was assessed before storage and then every semester until 18 months by germination and vigor tests. Variance tests were applied for statistical analysis and means were compared as a 4 x 4 factorial. Storage environments were compared by the Tukey test (p ≤ 0.05) and storage time by regression analysis. Speed and percentage of seedling emergence are reduced after 15-month storage of sudangrass seeds whereas seed germination, seedling development and seed weight are preserved until 18 months. Storing seeds under natural environment decrease vigor faster than conservation in dry chamber, frost free and freezer, although seedling growth is higher in that condition compared to the others.